Introduction: Reassessing French Studies in the Context of Postmodern Geopolitics - Dominique D. Fisher (Studies in 20th & 21st Century Literature, 2002)
This volume was compiled following the 16th International colloquium in Twentieth-Century French Studies that Martine Antle and I organized at UNC-Chapel Hill in 1999…
Keywords: French studies; geopolitics; postmodernism; review